PENERAPAN BERMAIN â€œTEMBAK IKANâ€ UNTUK MENINGKATKAN HASIL BELAJAR GERAK DASAR MELEMPAR PADA SISWA KELAS IV SEMESTER II SD NEGERI KUTOWINANGUN 01 KEC. TINGKIR KOTA SALATIGA TAHUN PELAJARAN 2012/2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
Classroom Action Research is motivated by the low base throwing motion learning outcomes achieved bystudents of SDN Kutowinangun 01, Salatiga, where only 32.5% of all students are able to achieve masteryKKM is 75. Classroom Action Research is a qualitative study, which lasted for 2 cycles involving all fourthgrade students of SDN 01 Kutowinangun Salatiga, containing 40 students. Based on the results that could, incycle 1, the average value of the cognitive value of the average student 26 of 30, for the affective, the averagestudent is a perfect 20 of 20, and for the value of psychomotor, reaching 37 of the maximum 50 points, whileaccumulative average value for this cycle is 83 out of a maximum 100, and completeness KKM reached 72.5%.In cycle 2 there is an increase in the cognitive and psychomotor aspects. For the cognitive aspect, the averagerose 1 point to 27. For the affective aspect, because it has a maximum value in cycle 1, then there is an increase,and survive on an average value of 20. For psychomotor value, the average value also rose 3 points to 40. Basedon the above results, it can be concluded that the shooting game and fish can increase the ability of studentlearning outcomes in basic throwing motion at the fourth grade students of SDN 01 Kutowinangun Salatiga.Penjasorkes Teachers are also advised to be aware of the physical limits of the students, so it could be moreappropriate in developing the material, so according to the ability of the students.